Flexischooling, an inclusive educational option: Blended learning and e-Learning in conservatoires - García-Díaz, Ana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This bibliographic review presents some issues regarding the lack of inclusive practices in musical education. These problems create situations that prevent diverse students from accessing musical training. In order to solve these limitations, the possibility of creating a flexible conservatoire is presented, where blended learning, inclusive practices and reflective learning must prevail. After the literature review analysis, it is concluded that it is feasible to implement Flexi schooling at the conservatoire level to enrich musical education.